Pseudo-Maxwellian Velocity Distribution Formed by the Pickup-like Process in Magnetic Reconnection - Usami, Shunsuke; Horiuchi, Ritoku (Frontiers in Astronomy and Space Sciences, 2022)
Focusing on ring-shaped ion velocity distributions with a finite width formed in magnetic reconnection in the presence of a guide magnetic field, intriguing properties such as the formation mechanism, a significant change in the shape, and necessary conditions for the change are investigated by means of theory and simulations. The width of a ring velocity distribution predominantly originates from velocity variations of seed particles for the pickup-like process. A function exactly representing a ring with a width is analytically formulated, assuming a steady supply of seed particles satisfying a Maxwellian velocity distribution and a mixing of gyration phases. The formulated function indicates that when the ring width is larger than a criterion, the local minimum of the ring’s center is changed into the maximum, and the shape is transformed into a mountain shape. Such a mountain-like distribution is defined as “a pseudo-Maxwellian distribution,” because it is almost indistinguishable in shape from a genuine Maxwellian distribution. Actually, particle simulations demonstrate that mountain-shaped ion velocity distributions are formed during magnetic reconnection with a guide magnetic field, and it is nearly concluded that they are pseudo-Maxwellian distributions. Moreover, two types of evidence for pseudo-Maxwellian distributions are shown by simulations. One is to analyze the dependence of the distribution shape on the guide magnetic field, which is explored by the particle simulation. In cases of slightly different values of the guide field, vague shapes of rings with a width are observed as ion velocity distributions. The other is to observe velocity distributions under a hypothetical condition of an artificial zero temperature in the upstream by utilizing a test particle simulation. In the test particle simulation, ring-shaped distributions with a width are clearly seen, because the velocity variations in the upstream are reduced. From the two types of evidence, it is definitely confirmed that the mountain-shaped distributions found in the particle simulations are pseudo-Maxwellian distribution. These results imply that pseudo-Maxwellian distributions would be created for various cases of guide field magnetic reconnection.